IL-27 regulates the number, function and cytotoxic program of antiviral CD4 T cells and promotes cytomegalovirus persistence. - Ellen J Wehrens; Kurt A Wong; Ankan Gupta; Ayesha Khan; Chris A Benedict; Elina I Zuniga (PLoS ONE)
The role of IL-27 in antiviral immunity is still incompletely understood, especially in the context of chronic viruses that induce a unique environment in their infected host. Cytomegalovirus (CMV) establishes a persistent, tissue localized infection followed by lifelong latency. CMV infects the majority of people and although asymptomatic in healthy individuals, can cause serious disease or death in those with naïve or compromised immune systems. Therefore, there is an urgent need to develop a protective CMV vaccine for people at-risk and identifying key regulators of the protective immune response towards CMV will be crucial. Here we studied mouse CMV (MCMV) in IL-27 receptor deficient animals (Il27ra-/-) to assess the role of IL-27 in regulating CMV immunity. We found that IL-27 enhanced the number of antiviral CD4 T cells upon infection. However, in contrast to a well-established role for CD4 T cells in controlling persistent replication and a positive effect of IL-27 on their numbers, IL-27 promoted MCMV persistence in the salivary gland. This coincided with IL-27 mediated induction of IL-10 production in CD4 T cells. Moreover, IL-27 reduced expression of the transcription factor T-bet and restricted a cytotoxic phenotype in antiviral CD4 T cells. This is a highly intriguing result given the profound cytotoxic phenotype of CMV-specific CD4 T cells seen in humans and we established that dendritic cell derived IL-27 was responsible for this effect. Together, these data show that IL-27 regulates the number and effector functions of MCMV-specific CD4 T cells and could be targeted to enhance control of persistent/latent infection.